Multilingualism and Plurilingualism in Teaching the Lingua Franca: A Critical Review - Marzieh Ebrahimi (Media and Intercultural Communication: A Multidisciplinary Journal)
This study investigates the groundbreaking and significant integration of plurilingualism and multilingualism within the context of teaching English as a Foreign Language (EFL). The incorporation of this approach presents a potential for redefining educational paradigms to promote inclusivity and equality. However, it also presents other issues that necessitate careful examination, including theoretical uncertainties, practical challenges, and constraints associated with critical pedagogy. The subject matter beyond the boundaries of academic discussion, exerting influence on the educational experiences of individuals globally, and necessitates an approach that is attuned to the specific situation. It is imperative to recognize the inherent complexities of languages, as they serve not only as means of communication, but also as cultural, authoritative, and individual manifestations. To address this intricate task in an effective manner, it is imperative for future scholars to embrace a dual approach characterized by boldness and humility, while acknowledging the extensive global ramifications involved. The achievement that could be attained in this domain requires a denial of overly simplistic resolutions and demands an active, intricate comprehension of the intricate aspects of language and education.